Using Paleoclimate and the Fossil Record to Explain Past and Present Distributions of Armadillos (Xenarthra, Dasypodidae) - Soibelzon, Esteban (2019)
Numerous climatic fluctuations occurred during the Cenozoic (last 66 Ma BP); some of them were drastic (e.g., during the Eocene-Oligocene boundary) while others were more gradual (e.g., late Tertiary cooling), but both have deep effect on the biotas. Armadillos are exclusively from the Americas; they have an old evolutionary history in South America and faunal replacement and/or local extinctions were detected, linked with climatic fluctuations. The global cooling of the late Eocene - early Oligocene coincides with a well-documented faunal turnover of Dasypodinae by Euphractinae in Patagonia. During cold and arid periods of the Quaternary, Euphractinae and Tolypeutinae moved more than once to the eastern Pampean Region, and Dasypodinae moved northward to central Brazil or even further north to the Guyana Region. During interglacial periods some armadillos went extinct locally and/or moved to Patagonia (Zaedyus), central Argentina (Tolypeutes matacus, Chaetophractus vellerosus), or from the north to Mesopotamia and the Pampean Region (Dasypus). Since the end of the Pleistocene/early Holocene, human activity has strongly impacted armadillo populations. Currently, the eastern Pampean Region (Argentina) is characterized by the presence of the couple C. villosus - D. hybridus (probably established since the late Holocene), but during the Pleistocene was Z. pichiy – T. matacus while Z. pichiy - C. villosus characterized early-middle Holocene. This work serves as evidence that paleozoological studies can be used to assess responses of biological systems to large scale perturbations and is the basis for studying future species distributions, in order to identify species in danger of extinction and establish management actions.